Discharge Planning Increase Therapy Obedient of Patients - Nursalam Nursalam; Sumiatun Sumiatun; Amirul Musrini (Jurnal Ners, 2008)
Introduction: Discharge planning is a nurses learning  process of patients  hospitalized in  the hospital. Discharge planning  includes all treatments given to the patients  from the time of admission, during hospitalization, until the time of discharge. The aimed of this study was to evaluate  the patient’s  compliance for therapy (oral and injection medicine, nutrition and activities). Method: A quasy experimental purposive sampling design was used in this study. There were 14 respondents with DHF and GE who met to the inclusion criteria. The independent variable was Discharge planning and the dependent variable was patient’s  compliance for therapy.  Data were collected by using questionaire of medicine, nutrition and activity then analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U Test with significance level α≤0.05. Result: The result showed that discharge planning had significance influence to patient’s  compliance for therapy (p= 0.028). Discussion: It can be concluded that discharge planning has an effect to increase patient’s  compliance for therapy (oral and injection medicine, nutrition and activities).